Penguatan Branding Produk Pangan Lokal melalui Pelatihan Penggunaan Chatbot dan Green Economy di Agrowisata Sukapulang Kabupaten Ciamis - Kiki Endah; Wiwin Setianingsih; Rian Dwicahya Supriatman; Dede Ahmad Suryana (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service activity aims to strengthen the branding of local food products through the utilization of chatbot technology and the application of the green economy concept at Sukapulang Agrotourism in Ciamis Regency. The partner faced challenges, including limited digital marketing strategies and insufficient understanding of the importance of a green economy in managing local food businesses. To address these issues, participants were introduced to the use of chatbots as an interactive web-based tool to improve promotion and customer service efficiency, alongside the implementation of green economy principles to enhance business sustainability.The program employed several methods, including educational outreach, hands-on practice in operating simple chatbots, and group discussions on sustainable branding strategies. Participants were guided to design practical applications of chatbot features for marketing and consumer interaction, while simultaneously exploring ways to integrate environmentally friendly practices into daily business operations. The training also emphasized strategies for reducing waste, optimizing resource use, and enhancing local product value through eco-conscious initiatives. Results indicate that participants experienced significant improvements in both knowledge and skills, particularly in combining digital technology with environmentally friendly business practices. They gained practical insights into how technological innovation can support marketing efforts, while green economy principles encourage long-term sustainability. This integration of digital tools and eco-friendly practices is expected to increase the competitiveness of local food products and strengthen Sukapulang Agrotourism’s position as a creative economy hub. Ultimately, the program demonstrates that community-based interventions leveraging digital innovation and environmental awareness can foster sustainable economic growth, enhance local entrepreneurship, and promote a more resilient and environmentally responsible business ecosystem.